The Effects of the Russia-Ukraine War on the Performance of High and Low ESG Portfolios : Evidence from Finland - Hirsimaa, Paulus (My University, 2025)
The integration of Environmental, Social, and Governance (ESG) considerations into investment strategies has become increasingly important in recent years, driven by various global sustaina bility goals, changing investor expectations, and evolving regulations. This thesis investigates the impacts of the Russia-Ukraine war on the financial performance of equity portfolios differenti ated by ESG ratings, using stocks from the Finnish stock market. Finland is a particularly relevant market for this study due to its strong ESG orientation and geographical proximity to the conflict. Two portfolios were constructed using the ESG scores retrieved from the LSEG DataStream, the first portfolio consisting of the 30 companies with the highest ESG ratings and another compris ing the 30 companies with the lowest ESG ratings. The analysis was conducted within four dif ferent time periods: Pre-War period, Early-War period, Mid-War period, and Late-War period, using daily stock return data beginning from January 2021 to March 2025. The OMX Helsinki Price Index (OMXHPI) is used as the market benchmark. The methodology merges an event study framework for measuring Cumulative Abnormal Returns (CARs) with a difference-in-dif ferences (DiD) regression approach to test whether the war introduced a structural shift in the relative performance of the portfolios. Findings indicate that during the early phase of the war, the high-ESG portfolio suffered notably smaller losses than the low-ESG portfolio and continued to outperform during the mid-war phase. However, the observed differences across all periods were not statistically significant. Furthermore, the high-ESG portfolio exhibited a slightly higher market beta, indicating greater sensitivity to broad market movements, which is contrary to the common assumption that ESG investments carry lower volatility. These results indicate that while portfolios with higher ESG scores might offer perceived resili ence during geopolitical crises, they do not yield statistically significant improvements in returns or risk reduction. This thesis contributes to the existing body of literature by providing rare, event-based evidence from a Nordic market directly affected by regional conflict. It also under scores the need for more detailed, sector-sensitive analysis in future ESG performance research.

Ympäristöön, sosiaaliseen vastuuseen ja hyvään hallintotapaan (ESG) liittyvien näkökohtien huomioon ottaminen sijoitusstrategioissa on viime vuosina noussut yhä merkittävämpään ase maan. Taustalla vaikuttavat muun muassa globaalit kestävän kehityksen tavoitteet, sijoittajien muuttuvat odotukset sekä sääntelyn kehitys. Tämä opinnäytetyö tarkastelee Venäjän ja Ukrai nan välisen sodan vaikutuksia osakesalkkujen tuottokehitykseen, jotka on koottu ESG-luokitus ten perusteella. Suomi tarjosi tutkimukselle sopivan tutkimusympäristön vahvan ESG-suuntau tumisensa ja maantieteellisen läheisyytensä vuoksi suhteessa sotaa käyvään alueeseen. Tutkimuksessa rakennettiin kaksi osakesalkkua LSEG DataStream -tietokannasta saatuihin ESG pisteytyksiin perustuen: toinen koostui 30 korkeimman ESG-arvon yrityksestä ja toinen 30 ma talimmat ESG-pisteet saaneesta yrityksestä. Analyysi kattoi neljä eri ajanjaksoa: ennen sotaa, sodan alkuvaiheen, keskivaiheen sekä myöhäisvaiheen, ja perustui päivittäisiin osaketuottoihin ajalta tammikuu 2021 – maaliskuu 2025. Vertailuindeksinä käytettiin OMX Helsinki Price Inde xiä (OMXHPI). Tutkimusmenetelmänä sovellettiin tapahtumatutkimusta kumulatiivisten epä normaalien tuottojen (CAR) mittaamiseen sekä difference-in-differences (DiD) -regressioanalyy siä sen arvioimiseksi, aiheuttiko sodan puhkeaminen rakenteellisen muutoksen salkkujen välis ten tuottoerojen kehitykseen. Tulokset osoittavat, että sodan alkuvaiheessa korkean ESG-arvon salkku kärsi selvästi vähäisem mät tappiot kuin matalan ESG-arvon salkku, ja suoriutui paremmin myös sodan keskivaiheessa. Erot eivät kuitenkaan olleet tilastollisesti merkitseviä. Lisäksi korkean ESG-arvon salkulla havait tiin hieman korkeampi markkinabeeta, mikä viittaa suurempaan herkkyyteen yleisiin markkina liikkeisiin ja on ristiriidassa sen oletuksen kanssa, että ESG-sijoitukset olisivat vähäriskisempiä. Tulokset viittaavat siihen, että korkean ESG-pisteytyksen saaneilla osakkeilla voi olla koettua va kautta kriisitilanteissa, mutta ne eivät tuottaneet merkittävästi parempia tuottoja tai matalam paa riskiä tilastollisesti merkittävällä tavalla. Opinnäyte tarjoaa harvinaista, tapahtumapohjaista näyttöä konfliktin vaikutusalueella sijaitsevalta pohjoismaiselta markkinalta, ja korostaa tar vetta tarkempaan, toimialakohtaiseen ESG-suoriutumisen tutkimukseen vastaavanlaisissa tilan teissa.
Keywords: responsible investing; Venäjän hyökkäys Ukrainaan 2022; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance